KONSEP MANAJEMEN KEUANGAN PRAKTIS DEMI PENINGKATAN KEMANDIRIAN UMKM Di KABUPATEN KUDUS - Darsin Darsin; Sukma Wijayanti; Nur Hayati (Universitas Muhammadiyah Semarang, 2025)
Empowerment of Micro, Small and MediumEnterprises (MSMEs) is currently showing a positivetrend.This shows that MSMEs have a strategicposition in national economic development, plays arole in development, employment and distribution ofdevelopment results. This research focuses onincreasing the financial independence of MSMEsthrough the application of financial managementconcepts that are practical and easy to understand.The research methods used include a survey ofKudus district MSME players, in-depth interviews withbusiness owners, as well as analysis of availablefinancial data. This research seeks to obtain theconcept of practical financial management to increaseindependence for MSMEs in Kudus Regency byincluding determining samples using the purposivesampling method, collecting data and then testing itusing PLS (Partial Least Square). The test results intheresearchshowthatpracticalfinancialmanagement has a positive effect on independence.Kudus district MSMEs with a statistical t value of4.722 and an original sample estimate value of 0.432and financial management has a positive impact onKudus district MSMEs with a statistical t value of5.999 and an original sample estimate value of 0.550.